Writing Anxiety Among Indonesian EFL Students in Online Discussion Forum - Mahendra, Zulkifli Ihza; Arifin, Syaadiah; Ilyas, Hamzah Puadi (PROJECT (Professional Journal of English Education), 2025)
In the context of online learning increasingly adopted by an Indonesian higher education institution, students must adapt to new modes of instruction, which may lead to anxiety, particularly in EFL writing through online discussion forums. This study aims to identify and describe the types, levels, and contributing factors of writing anxiety, as well as how students manage their anxiety in online discussion settings. A mixed-methods approach with a concurrent triangulation design was used to understand the phenomenon. Data were collected through questionnaires and interviews with twenty-five first-semester master's students in the English Education Study Program at a private university in Jakarta.The findings revealed that most students experienced moderate anxiety, with cognitive anxiety being the most prevalent type. Contributing factors included linguistic difficulties, fear of negative comments, and time pressure. Furthermore, the study highlights the importance of supportive instructional strategies and self-regulation in reducing writing anxiety among EFL learners in digital contexts.